Barriers and facilitators to patients' adherence to antiretroviral treatment in Zambia: a qualitative study - Nawa Sanjobo; Jan C Frich; Atle Fretheim (Taylor & Francis Group, 2008)
Patients' adherence to antiretroviral therapy (ART) is important for effective medical treatment of HIV/AIDS. We conducted a qualitative interview study in the Copperbelt Province of Zambia in 2006. The aim of the study was to explore patients' and health care professionals' perceived barriers and facilitators to patients' adherence to ART. Based on data from individual interviews and focus group interviews with a total of 60 patients and 12 health care professionals, we identified barriers and facilitators related to patients' beliefs and behaviours, the health service, and socio-economic and cultural factors. Among the barriers we identified were lack of communication and information about ART, inadequate time during consultations, lack of follow-up and counselling, forgetfulness, stigma, discrimination and disclosure of HIV status, lack of confidentiality in the treatment centres, and lack of nutritional support. Feeling better, prospects of living longer, family support, information about ART, support for income-generating activities, disclosure of HIV status, prayers and transport support were among the facilitators. Our study suggests that several issues need to be considered when providing ART. Further research is needed to study interactions between patients and their health care providers. Our findings can inform interventions to improve adherence to ART.